Microplastic pollution in commercially important edible marine bivalves: A comprehensive review - Zhixiong Xu; Leiheng Huang; Peng Xu; Lim Leong Seng; Cheong, Kit-Leong; Youji Wang; Karsoon Tan (Elsevier B.V., 2024)
Microplastics have become major pollutants in the marine environment and can accumulate in high concentrations, especially in the gut of marine organisms. Unlike other seafood, bivalves are consumed whole, along with their digestive systems, resulting in the transfer of microplastics to humans. Therefore, there is an urgent need to review the status of microplastic pollution in marine bivalves. In this context, this article provides a comprehensive review of the status of microplastic pollution in marine bivalves and the impact of microplastics on the physiology and immunology of marine bivalves. In general, marine bivalves can accumulate high levels of microplastics in a tissue-specific manner. Although microplastic pollution does not cause mortality in bivalves, it can adversely affects bivalves' immunity, byssus production, and reproduction, potentially affecting bivalve populations. This article provides important information that will aid establishing management measures and determining the direction of future research.